1982
DOI: 10.1680/macr.1982.34.121.213
|View full text |Cite
|
Sign up to set email alerts
|

The anchorage capacity of reinforcing bars at normal and high temperatures

Abstract: Synopsis The anchorage failure of reinforcing bars is analysed, and it is shown that two modes of failures are possible: splitting or bond failure. It is concluded that the anchorage capacity cannot be estimated by means of a standard specimen, since splitting failure is dependent upon the geometry of the cross-section. A simple method for calculating the resistance to splitting is proposed, and a test method for determining the bond strength is presented. Test results are shown from a series of 280 specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 0 publications
0
28
0
1
Order By: Relevance
“…Node segments may contain facilities for anchorage of prestressed or slack reinforcement, and the size and shape can be designed to utilise compression stresses from bearings and compression zones to improve the anchorage capabilities by counteracting splitting stresses. 12 A multitude of anchorage details and prestressing methods are available as shown for example by Leonhardt 13 and Gerwick,14 in addition to the original methods described by Freyssinet.…”
Section: Connectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Node segments may contain facilities for anchorage of prestressed or slack reinforcement, and the size and shape can be designed to utilise compression stresses from bearings and compression zones to improve the anchorage capabilities by counteracting splitting stresses. 12 A multitude of anchorage details and prestressing methods are available as shown for example by Leonhardt 13 and Gerwick,14 in addition to the original methods described by Freyssinet.…”
Section: Connectionsmentioning
confidence: 99%
“…If axial forces are to be transferred between light concrete and a pearl-chain, the anchorage capacity can be assessed as a minimum of splitting strength and bond strength using the formulae in Hertz. 12 The bond strength is proportional to the diameter and the compressive strength of the concrete. The low bond strength of the light concrete is counteracted by the large diameters of the pearl-chain segments.…”
Section: Connectionsmentioning
confidence: 99%
“…The different studies showed a significant effect of steel rebar surface characteristics, concrete confinement, concrete basic properties (w/c ratio, cement and aggregate type, additives), maturity, and relative humidity, and testing condition (heating and cooling duration and rate, and testing while hot or cold) on concrete-steel bond behavior under a wide range of high temperature conditions [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The works published about the mechanical performance of plain and RC under elevated temperatures stipulated the benefit of using pozzolanic matter and carbonate aggregate as well as insulation of concrete against moisture intrusion on maintaining post-heating strength and the concretesteel bond [10][11][12][13][14][15][16][17][18][19]. Recently, there has been an increasing interest in using metallic and polymeric fibers in ordinary and high strength concrete mixtures to improve the resistance of the concrete to elevated temperatures of up to 1000 1C [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…This subject has therefore been a main area of his research for 25 years, leading to a system of methods for design of beams, slabs, columns, walls and analyses of anchorage and spalling based on a continuous material research programme and supplemented with full-scale tests for verification of the design methods. This work will be documented in a series of papers mainly intended for MCR, where the present deals with basic idealised materials data for reinforcement, except the anchorage capacity, which has been published in Hertz 1 and quenched qualities, which will be treated separately.…”
Section: Introductionmentioning
confidence: 99%